Autophagy in neuronal cell loss: a road to death. - Takacs-Vellai (BioEssays, 2006)
The regulation of ageing has been extensively studied in divergent animal model systems including worms, flies and mice. However, little is known about the cellular pathways that mediate the death of these organisms. Analysing major cellular changes in the ageing nematode Caenorhabditis elegans has revealed a gradual, progressive deterioration of different tissues except for the nervous system, which remarkably preserves its integrity even in advanced old age. In addition, genetic data have shown that, in C. elegans and in the fruit fly Drosophila melanogaster, lifespan is controlled by signals derived from neurons and acting throughout adulthood. Organismal death thus seems to be a consequence of the decline of specific neurons. Accumulating evidence demonstrates that late onset of neuronal cell loss generally occurs via autophagy, a process in which eukaryotic cells self-digest parts of their contents during development or to survive starvation. Here we suggest that overactivation of autophagy in the cells of the nervous system is the eventual cause of "physiological" death.